Efektivitas Lapak Baca di Taman Baca Masyarakat (TBM) Tanah Ombak terhadap Minat Baca Anak di Kawasan Purus Kota Padang - Saskia, Aida; Nelisa, Malta (Lembaga Yasin AlSys, 2024)
This study aims to describe: (1) the target accuracy of the reading stall program at TBM Tanah Ombak; (2) the socialization of the reading stall program at TBM Tanah Ombak; (3) the objectives of the reading stall program at TBM Tanah Ombak; (4) the monitoring of the reading stall program at TBM Tanah Ombak; (5) children's reading interest in the Purus area of Padang City; (6) the effectiveness of the reading stall at TBM Tanah Ombak on children's reading interest in the Purus area of Padang City. The sample in this study consisted of 100 children. The sampling technique used in this study is simple random sampling. Data collection techniques include questionnaires, interviews, and literature studies. Based on the research results, it was found that: (1) the target accuracy of the reading stall program at TBM Tanah Ombak is in the excellent category with an average score of 3.67, indicating that children's reading interest increased with the presence of the Tanah Ombak reading stall; (2) the socialization of the Tanah Ombak Reading Stall program is in the good category with an average score of 3.14, which can be seen from the number of children coming to the Tanah Ombak Reading Stall; (3) the objectives of the Tanah Ombak Reading Stall program are in the excellent category with an average score of 3.57, indicating that the program's benefits are felt by the children; (4) the monitoring of the Tanah Ombak Reading Stall program is in the good category with an average score of 3.20, showing that the program has achieved its set goals and is still ongoing; (5) children's reading interest in the Purus area of Padang City is in the excellent category with the presence of the Tanah Ombak Reading Stall, with an average score of 3.60, which is evident from the number of children who enjoy reading and regularly visit the reading stall to participate in literacy activities; (6) the effectiveness of the Tanah Ombak Reading Stall on children's reading interest in the Purus area of Padang City is in the excellent category with an average score of 3.40, indicating that the Tanah Ombak Reading Stall is effective in increasing children's reading interest in the Purus area of Padang City.